Effects of Age and Disease Duration on Excess Mortality in Patients With Multiple Sclerosis From a French Nationwide Cohort. (27th July 2021) - Rollot, Fabien; Fauvernier, Mathieu; Uhry, Zoe; Vukusic, Sandra; Bossard, Nadine; Remontet, Laurent; Leray, Emmanuelle; Brochet, Bruno; Casey, Romain; Cotton, François; De Sèze, Jérôme; Mansuy, Lucilla; et al.
Abstract : Objective: To determine the effects of current age and disease duration on excess mortality in multiple sclerosis (MS), we describe the dynamics of excess death rates over these 2 time scales and study the effect of age at MS clinical onset on these dynamics, separately in each initial phenotype. Methods: We used data from 18 French MS expert centers participating in the Observatoire Français de la Sclérose en Plaques. Patients with MS living in metropolitan France and having a clinical onset between 1960 and 2014 were included. Vital status was updated on January 1, 2016. For each MS phenotype separately (relapsing onset [RMS] or primary progressive [PPMS]), we used an innovative statistical method to model the logarithm of excess death rates by a multidimensional penalized spline of age and disease duration. Results: Among 37, 524 patients (71% women, mean age at MS onset ± SD 33.0 ± 10.6 years), 2, 883 (7.7%) deaths were observed and 7.8% of patients were lost to follow-up. For patients with RMS, there was no excess mortality during the first 10 years after disease onset; afterwards, whatever the age at onset, excess death rates increased with current age. From current age 70, the excess death rate values converged and became identical whatever the age at disease onset, which means that disease duration had no more effect. Excess death rates were higher in men, with an excess hazard ratio of 1.46 (95% confidence interval 1.25–1.70). In contrast, in patients with PPMS, excess death rates rapidly increased from disease onset, and were associated with age at onset, but not with sex. Conclusions: In RMS, current age has a stronger effect on MS mortality than disease duration, while their respective effects are not clear in PPMS.